BIOFILM-FORMING PROPERTIES OF PATHOGENIC MICROORGANISMS IN CHILDREN WITH RECURRENT TONSILLITIS - Kravets, N.Ya.; Klumnyk, S.I.; Romanyuk, L.B.; Borak, V.P. (World of Medicine and Biology, 2022)
Among the causes of chronic infection and resistance to antibiotic treatment are the formation of biofilms in the respiratory tract in respiratory infections. The purpose of the study is to identify the ability to film strains of S. aureus on the surface of the epithelial tissue of the oropharynx isolated from patients with recurrent tonsillitis. Clinical strains of Staphylococcus spp bacteria obtained from the oropharynx of 42 children with recurrent tonsillitis were investigated. The ability to form biofilms – when grown on 96-well plastic plates and on the surface of coverslips for three days. It was found that 12 (28.58 %) strains out of 42 had film-forming ability, among which 3 (7.14 %) strains showed strong film-forming, 8 (19.04 %) strains were moderate, one strain (2.38 %) – a moderate formation film and 30 strains (71.4 %) lacked this ability. The severity of staphylococcus film formation was determined by optical density at a wavelength of 550 nm. Conducted studies of the intensity of film formation over three days of cultivation, the rate of OD was 0.054
Keywords: biofilm; recurrent tonsillitis; degree of biofilm formation; Staphylococcus spp